Lipocalin‐Type Prostaglandin d Synthase Conjugates as Magnetic Resonance Imaging Contrast Agents for Detecting Amyloid β‐Rich Regions in the Brain of Live Alzheimer's Disease Mice. Issue 11 (2nd August 2021) - Sharma, Bhargy; Grandjean, Joanes; Phillips, Margaret; Kumar, Ambrish; Mandino, Francesca; Yeow, Ling Yun; Low, Kimberly Jia Yi; Nandwana, Vikas; Dravid, Vinayak P.; Bengang, Xing; Lim, Sierin; Pervushin, Konstantin
Abstract : With a significant proportion of the global population growing older (>60 years), the low success rates of current diagnoses for early neurodegeneration signs are disappointing. Early detection of Alzheimer's disease (AD) can improve acclimatization and quality of life for patients in their later years. Endogenous proteins, such as the most abundant secreted protein in cerebrospinal fluid, lipocalin‐type prostaglandin d synthase (L‐PGDS), can bind the early toxic oligomers of amyloid β (Aβ) peptides implicated in AD and prevent their aggregation. Herein, the utility of L‐PGDS for detection of amyloids is demonstrated. L‐PGDS is conjugated with different iron‐oxide magnetic nanoparticles for contrast‐enhanced visualization using magnetic resonance imaging (MRI). These conjugates inhibit amyloid aggregation in vitro and improve viability in neuronal cells incubated with amyloid fibrils, showing a potential neuroprotective function. L‐PGDS‐ferritin conjugates, when administered intraventricularly, localize to AD‐associated amyloid‐rich regions in mice brain imaged using MRI and histological stains. As a proof‐of‐concept, it is demonstrated that L‐PGDS conjugates could reach the brain regions through non‐invasive intranasal administration. These conjugates are developed as the first entirely protein‐based nanoprobes for early detection of brain amyloids. The results of this study open a wider avenue for study of endogenous proteins as potential theranostics for AD. Abstract : Lipocalin‐type prostaglandin d synthase (L‐PGDS) conjugated with ferritin nanocages is the first ever reported magnetic resonance imaging (MRI) probe where the targeting agent and the contrast agent are both proteins. These conjugates bind to amyloid fibrils in vitro and enhance T2 contrast in MRI, thus function as a diagnostic agent for detection of amyloids in Alzheimer's disease (AD) mouse brain.